(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Seed spices are an important category of agricultural commodities that contribute significantly to our country’s economy. India has long been known as a spice producing country. Coriander, cumin, and fennel are members of the umbelliferon family, whereas fenugreek belongs to the Fabaceae family. Bioactive compounds, also bioactive constituents, are occurs naturally, physiologically active phytochemicals that operate as a natural defence mechanism for host plants or have previously been exploited as medications, perfumes, or taste components. They’re a gold mine of opportunities in our search for useful bioactive molecules for pharmacotherapy or other wellness issues. Seed spices affect a number of biological systems, such as the digestive, circulatory, reproductive, or neurological systems, causing a range of metabolic but also physiologic consequences. Antioxidants, antidiabetic, anticancer, antimicrobial activity, hypolipidemic influence, insecticidal, beneficial in heavy menstrual bleeding, aiding digestion, high blood pressure, instrumentation of enzymes involved, immune function, reduction of inflammatory process, molecular mechanism, modulations of immune systems, The purpose of this research is to have a thorough analysis on the present trends in research here on health advantages of four common seed seasonings: cumin, coriander, but also fennel.